GE power : General Electric's sputtering engine - Mukherjee, Kaushik, (SAGE business cases, 2021)
General Electric (GE) is a diversified industrial conglomerate with interests in power, aviation, industrial electronics, and financial services. A subsidiary of GE, GE Power manufactures primarily gas turbines, steam turbines, grid solutions, and support equipment for the power generation industry. General Electric acquired Alstom's power generation and transmission business in 2015 and absorbed it into the GE Power business. After the acquisition, renewable energy gradually became competitive with conventional sources of energy. As Alstom's portfolio was focused on conventional sources of power, the acquisition did not accrue value for GE Power as expected. Instead, it created redundancies for GE and led to post-acquisition integration problems. Larry Culp, the incumbent CEO of GE is pondering some strategic options available to revive the power business. Some options include divestiture of GE Power or bringing in new investors. Another option is restructuring the business into two separate business verticals for gas turbine and steam turbine business. He faces a dilemma to decide which option would be the optimal future strategy for GE Power.